Microbiology of Indian Chutneys - Bansal, Sunita (My University, 2007)
Green chutneys served with ready- to- eat foods in Patiala city were analyzed for their microbiological quality.Quantitative analysis showed significant loads of total viable bacteria,faecal coliforms and staphylococcus. Qualitative analysis revealed the presence of coagulase positive S.aureus, Salmonella enteriditis and E.coli O157:H7;non pathogenic (surrogate)strains of S.aureus and E.coli O157:H7 were used to study the behavior of the latter in coriander base and green chutneys (prepared from this base) at different abusive storage temperatures, for extended as well as short time periods.None of the strains were found to grow but S.aureus continued to survive without decline in numbers especially at refrigeration temperatures, for 24hours; the trend of survival observed with both high and low inoculum sizes of S.aureus was similar. Acid stressed E.coli O157:H7 exhibited a longer sustainence than its unstressed counterpart in both coriander base and green chutneys. Based on the short term survival data of both these bacterial pathogens and those available from dose response studies of these pathogens, the risk calculated for average serving sizes was significantly high for consumers.
Keywords: Microbiology; Indian Chutneys